Effect of Correlation on BER Performance of the FSO-MISO System With Repetition Coding Over Gamma–Gamma Turbulence - Richa Priyadarshani; Manav R. Bhatnagar; Zabih Ghassemlooy; Stanislav Zvanovec (IEEE Photonics Journal, 2017)
In free space optical (FSO) communication systems, atmospheric turbulence is the major cause of bit error rate (BER) performance degradation. The error performance of the system can be significantly improved with the help of spatial diversity by employing multiple transmit or receive apertures. However, correlation of channels under turbulence in the case of small separation between transmit apertures can substantially reduce the benefits of spatial diversity. Still, a thorough analysis of the system performance in terms of diversity order and coding gain for the FSO multiple-input single-output (MISO) system under turbulence influenced correlated channels has not been studied when the repetition coding is used to achieve improved BER performance. In this paper, we provide unique results of the BER performance analysis of the considered correlated FSO-MISO system over Gamma–Gamma distributed turbulence channel. Using the joint moment generating function of received signal-to-noise ratio (SNR), a novel generalized approximate BER expression is derived, followed by convergence test of the power series based BER expression using the Cauchy's ratio test. Then, an asymptotic analysis at high SNR is performed to obtain a novel closed-form expression for BER of FSO-MISO system. We also derive expressions for coding gain, diversity gain, and coding gain loss due to correlation in channels. Although the effect of correlation in channels on the BER performance of the system is analyzed under different scenarios, while it is observed that it does not affect the diversity order; it significantly degrades the coding gain of the considered system.